Effects of Agility Training on Dribbling Performance among High School Futsal Players: An Experimental Study - Muhammad Taufik; Umar; Naluri Denay; Bram Sujadesman (STKIP Pasundan, 2026)
This study aimed to determine the effect of agility training on the dribbling ability of futsal extracurricular students at SMA Negeri 1 Lubuk Sikaping. The study was motivated by students’ low dribbling skills, including poor ball control and difficulty changing direction during play. A quasi-experimental method with a Two-Group Pretest–Posttest Design was used. The population consisted of 28 male students who participated in the futsal extracurricular program during the 2026/2027 academic year. Using total sampling, the students were divided into an experimental group and a control group, each consisting of 14 students. Data were collected using the Bobby Charlton Zig-Zag Dribbling Test and analyzed using t-tests with SPSS 26. The results showed that agility training significantly improved dribbling ability (t = 7.177; p < 0.05). The experimental group’s mean score improved from 20.30 seconds to 17.22 seconds. It was concluded that agility training effectively improves students’ dribbling ability.